Spatiotemporal coupling coordination between ecological environmental quality and urbanization level and influencing factors of eco-environment: a case study of Jiangsu, China - Luo, Qingqu; Guan, Yuwei; Lei, Xiangqi (Frontiers in Environmental Science, 2025)
The rapid acceleration of urbanization, coupled with intensified human activities, has exacerbated the tension between human development and the ecological environment. This issue is particularly pronounced in Jiangsu Province, a major economic and commercial hub in China. Achieving a balance between ecological environmental quality and urbanization levels is critical for promoting regional sustainable development, with significant implications for both ecosystem management and urban planning. To investigate the intricate interactions between the ecological environment and urbanization in Jiangsu Province, we employed the Modified Remote Sensing Ecological Index (MRSEI) model, utilizing Google Earth Engine (GEE) and MODIS imagery to construct an ecological environmental quality assessment for the province from 2002 to 2022. Concurrently, the Population–Economic–Sociology–Space (PESS) model, combined with socioeconomic data and the Analytical Hierarchy Process–Criteria Importance Through Intercriteria Correlation (AHP-CRITIC) weighting method, was used to develop the Urbanization Level Index (ULI). The coupling coordination degree (CCD) model was applied to analyze the coordination relationship between the ecological environment and urbanization, while the Geodetector was used to identify the key factors influencing the MRSEI. The findings include: (1) the MRSEI incorporates more comprehensive indicator information than the RSEI and demonstrates greater sensitivity in capturing greenness and dryness variations in Jiangsu Province; (2) the ecological environment in northern Jiangsu has shown steady improvement, whereas southern Jiangsu experienced significant deterioration from 2002 to 2010, followed by recovery and stabilization from 2010 to 2022; (3) the urbanization level in southern Jiangsu is higher and has grown rapidly, while urbanization in northern Jiangsu accelerated after 2014 but remains at a lower level compared to the south; (4) the urbanization lag in northern Jiangsu and the eco-environment lag in southern Jiangsu have both improved, enhancing the overall coordination between ecological environment and urbanization; and (5) Jiangsu Province exhibits a significant heat island effect, with improvements in greenness, heat, and dryness having a positive influence on the MRSEI. This research provides an analytical framework and theoretical insights to address the persistent conflict between urbanization and ecological sustainability. The findings offer a scientific basis for policy formulation, supporting regional sustainable development strategies and urban planning in rapidly urbanizing areas.